(untitled) (Journal of Life and Earth Science, 2011)
Urbanization of Bangladesh is developed by the natural growth of city, sub-urban growth, sub-urban transformation to urban area, and attaining new urban centers. Accordingly, growth of major urban centers depends on natural growth of city, suburban growth, sub-urban transformation and change in development level of sub-urban areas. As a result, the economy of those areas changes over time and the changes are controlled by a number of factors that playing increasingly dominated roles on the urban as well as national economy of Bangladesh. In the research an attempt has been made to identify the factors that have been influencing the economic transformation, the consequences of transformation in the area, and adopted governmental policies and programmes to develop them. Necessary data and information have collected from both primary and secondary sources for the study, and to analysis and represent of collected data quantitative analysis and mapping techniques have been applied. The research findings indicate that the change in economic setting of those areas in term of occupation, income, expenditure, land use, agricultural practices, infrastructure and facilities and so on is dependent on a set of factors such as distance, market demand, growth center, land availability and land value, employment opportunity, facilities and governmental development policies and programmes. Key words: Economic transformation; factors of economic transformation; sub-urban areas DOI: 10.3329/jles.v5i0.7350 J. Life Earth Sci., Vol. 5: 47-55, 2010